Reading Augustine’s Confessions in Normandy in the 11th and 12th Centuries - Lauren Mancia (Tabularia)
Scholars such as Pierre Courcelle have observed an intensification in interest in Augustine’s Confessions in medieval Europe after the 11th century. This intensification was manifested in Normandy in two ways: first, in the early 11th century, Abbot John of Fécamp drew extensively from Augustine’s Confessions in his own Confessio Theologica; and second, book lists and extant manuscripts from the Norman monastic world show a marked increase in the number of copies of Confessions in Normandy by end of the 12th century. This article offers, for the first time, both an analysis of how John of Fécamp used Augustine’s work in his own Confessio and an interpretation of the manuscript evidence for the diffusion of Confessions in Normandy. This study hopes to demonstrate how an analysis of contemporary intellectual interpretations of texts in Normandy can be used alongside paleographical examination of surviving copies to uncover both the ways in which and the reasons for which books circulated among the monastic houses.